REPRESENTASI NILAI FORMAL TEKS FAKTUAL PADA BUKU PELAJARAN BAHASA INDONESIA FASE D KURIKULUM MERDEKA; MODEL NORMAN FAIRLOUGH - Johar Amir; Ambo Dalle; Shafariana; Tuti Wijayanti (LPPM Politeknik Saint Paul Sorong, 2026)
This research is motivated by the importance of textbooks as a strategic medium in shaping students' values, character, and way of thinking in the implementation of the Merdeka Curriculum. Factual texts in Phase D Indonesian language textbooks not only convey information, but also represent formal values ​​related to experiential, relational, and expressive aspects. This study aims to identify and analyze the representation of formal values ​​in vocabulary and grammar in factual texts in Phase D Indonesian language textbooks using Norman Fairclough's Critical Discourse Analysis approach. Data collection methods were carried out through documentation, reading, and note-taking techniques for factual texts in textbooks for grades VII, VIII, and IX. Data analysis used Fairclough's three-dimensional model which includes text analysis, discourse practices, and socio-cultural practices. The results of the study indicate that experiential, relational, and expressive values ​​are represented through variations in vocabulary such as synonyms, antonyms, hyponyms, as well as the use of formal and informal language, and through grammatical structures such as active, passive, and modal sentences. Qualitatively, factual texts contain ideological content that reflects values ​​of discipline, religiosity, modernity, and social awareness. Quantitatively, the use of experiential and expressive vocabulary is more dominant than relational vocabulary. These findings indicate that factual texts in textbooks are not neutral but play a role in shaping students' critical awareness and social values.